KNOWLEDGE AND ATTITUDES ON DRUG PREVENTION AMONG FIRST-YEAR MEDICAL STUDENTS AT UNIVERSITY OF MEDICINE AND PHARMACY, THAI NGUYEN UNIVERSITY AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the knowledge and attitudes regarding drug prevention among first-year medical students at University of Medicine and Pharmacy, Thai Nguyen University and some related factors.Subjects and methods: A cross-sectional descriptive study was conducted on all first-year medical students at University of Medicine and Pharmacy, Thai Nguyen University, meeting all the inclusion and exclusion criteria of the study.Results: The percentage of students with good knowledge about drugs and their harmful effects reached 92.9%, while only 29.5% had good knowledge about the law on drug prevention. 86.9% of students had a correct attitude towards drug prevention. Up to 17.2% of students lacked the confidence to refuse drugs when tempted by friends. There was no correlation between some characteristics of the study subjects and knowledge and attitudes towards drug prevention; female students had a more positive attitude towards drug prevention than male students.Conclusion: Students have good knowledge of the harmful effects of drugs and a positive attitude towards prevention, but are limited in their understanding of the law and refusal skills. Legal education and prevention skills need to be strengthened in the school environment.
Keywords: Knowledge and adtitudes towards drug prevention, students, school environment.